Quality in paediatric emergency medicine: Measurement and reporting. (February 2016) - Borland, Meredith L; Shepherd, Mike
Abstract: There is a clear demand for quality in the delivery of health care around the world; paediatric emergency medicine is no exception to this movement. It has been identified that gaps exist in the quality of acute care provided to children. Regulatory bodies in Australia and New Zealand are moving to mandate the implementation of quality targets and measures. Within the paediatric emergency department (ED), there is a lack of research into paediatric specific indicators. The existing literature regarding paediatric acute care quality measures has been recently summarised, and expert consensus has now been reported. It is clear that there is much work to be performed to generalise this work to ED. We review suggestions from the current literature relating to feasible indicators within the paediatric acute care setting. We propose options to develop a quality 'scorecard' that could be used to assist Australian and New Zealand EDs with quality measurement and benchmarking for their paediatric patients.